Close up and far out : seeing the world differently - Auld, Mary; Meserve, Adria (Creative Editions, 2024)
"An illustrated picture book of early scientists Antonie van Leeuwenhoek and Galileo Galilei, who used similar observation tools but saw the world very differently, their discoveries leading to innovations in both microscopes and telescopes." --